Zoltán Kaposi – Virág Rab (eds.): Different Approaches to Economic and Social Changes: New Research Issues, Sources and Results.: Working Group of Economic and Social History Regional Committee of the Hungarian Academy of Sciences in Pécs, 2022. - Czina, Sára (Közép-Európai Közlemények, 2023)
-